1995
DOI: 10.3758/bf03206510
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and cognitive processes in time-to-contact estimation: Analysis of prediction-motion and relative judgment tasks

Abstract: Three classes of task appear to involve time-to-contact (TTC) information: coincidence anticipation (CA)tasks, relative judgment (RJ) tasks, and interceptive actions (lAs). An important type of CA task used to study the perception of TTCis the prediction-motion (PM) task. The question of whether it is possible to study the perceptual processes involved in the timing of lAs using PM and RJ tasks is considered. Arevised version of the tau hypothesis is proposed as an account of the perceptual information process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
302
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(323 citation statements)
references
References 86 publications
19
302
2
Order By: Relevance
“…In sum, it can be inferred that indirect interceptive actions involve a ballistic-type (e.g., Shea, 1980) or impulse-type of control (Tresilian, 1995). The intervention of mechanisms permitting regulation of the movement during its execution could be therefore excluded (e.g., Schmidt & Russel, 1972).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, it can be inferred that indirect interceptive actions involve a ballistic-type (e.g., Shea, 1980) or impulse-type of control (Tresilian, 1995). The intervention of mechanisms permitting regulation of the movement during its execution could be therefore excluded (e.g., Schmidt & Russel, 1972).…”
Section: Resultsmentioning
confidence: 99%
“…TTC ϭ time to contact. retical issue is raised by authors who have questioned the general and exclusive character of the tau hypothesis and suggested that other sources of information could be used to time actions (e.g., Michaels et al, 2001;Tresilian, 1995Tresilian, , 1999aTresilian, , 1999b.…”
Section: Timing Of Interceptive Actions With Acceleratedmentioning
confidence: 99%
“…As in the previous experiments, distractor objects with a TTP either earlier or later than target TTC were presented. As Tresilian (1995) has pointed out, in a PM task the observers are required to delay their response after the disappearance of the target from the screen, and thus "cognitive" mechanisms such as clocking or cognitive motion extrapolation are likely to play a role. In contrast, in the AI task, this type of cognitive influences is minimized (cf.…”
Section: Experiments 5: Pm Taskmentioning
confidence: 99%
“…A large body of literature suggests that the visual system possesses a dedicated processor that continuously computes tau. The constantly available tau information is then taken by the visual system to inform decisions such as when to start swinging the baseball bat or when to initiate a braking motion (see, e.g., Tresilian, 1995). More recently, a growing body of literature has suggested that the processor uses simpler, alternate optical variables, such as expansion rates or even simple image velocities (see, e.g., Kerzel, Hecht, & Kim, 2001;Smith, Flach, Dittman, & Stanard, 2001).…”
Section: The Current State Of Ttc Theorymentioning
confidence: 99%
See 1 more Smart Citation